(untitled) (Jurnal Bahasa, 2018)
This article will discuss the question word brapa that focuses on open-ended questions in the Perlis dialect, using the minimalist programme framework. The data analysed in this article was obtained through a field study conducted in the state of Perlis. The data was obtained through recording of native speakers of Perlis dialect. The researcher employed two research methods, namely library research and fieldwork. The researcher conducted library research to gather information related to question words, while fieldwork was carried out to obtain the data. The area for the field research covered all the districts within the political border of Perlis. Each district was divided into squares on a scale of 5km:1cm, covering the areas of the north, south, east and west. The data collected was analysed using the minimalist programme. The analysis shows that the in-situ or moved question word is related to the features of the question brapa itself, and also the OP feature that prevents its movement. As a result, the question word brapa in the Perlis dialect is moveable and also in-situ when it is associated with the position and presence of the OP in the Spec CP position. This theoretical analysis proves that the native speakers of the Perlis dialect have open-ended words that have both in situ and movable properties. Keywords: open-ended question words, close-ended question words, Perlis, features, dialect